Immunoinflammatory markers SIRI and NAR as predictors of respiratory distress syndrome and secondary infections in premature infants - Xuexin Chen; Yuedong Li; Hongxiang Chen; Weiming Chen (Frontiers in Cellular and Infection Microbiology)
BackgroundPremature infants are at high risk for neonatal respiratory distress syndrome (RDS) and secondary infections. This study aims to investigate the association between immunoinflammatory markers—the systemic immune inflammation index (SII), systemic inflammation response index (SIRI), and neutrophil-to-albumin ratio (NAR)—and the risk of developing RDS in premature infants.MethodsA total of 2164 premature infants were enrolled in this retrospective study. The clinical records of these neonates (respiratory tract infections, adverse pregnancy history, placental abnormalities, birth weight, Apgar scores, and immunoinflammatory indices) were collected. Comparisons were made between infants with and without RDS. Logistic regression analysis was used to evaluate the relationship between SII, SIRI, NAR and RDS.ResultsAmong the cohort, 962 infants developed RDS, while 1202 did not. The RDS group showed higher proportions of mothers with adverse pregnancy history, placental abnormalities, birth weight <2.5 kg, and lower Apgar scores at 1 and 5 minutes (all p<0.05). SII, SIRI, and NAR levels were significantly elevated in RDS infants (p<0.05). Logistic regression revealed that adverse pregnancy history (OR: 1.390, p=0.001), placental abnormalities (OR: 2.499, p<0.001), birth weight <2.5 kg (OR: 4.165, p<0.001), high SIRI (OR: 1.338, p=0.035), and high NAR (OR: 1.639, p<0.001) were significant predictors of RDS. Additionally, secondary infections, particularly pneumonia and sepsis, were significantly more common in the RDS group (p<0.001).ConclusionAdverse pregnancy history, placental abnormalities, low birth weight, elevated SIRI and NAR were associated with increased risk of RDS and secondary infections in premature infants. These findings suggest that SIRI and NAR could serve as useful markers for early identification and management of RDS and its complications in this vulnerable population.